Christmas Chaos : Hidden Picture Puzzles - Kalz, Jill; Yamasaki, James (North Mankato, MN : Picture Window Books, 2013)
"Illustrated scenes related to Christmas and winter invite readers to find a list of objects hidden within them"--Provided by publisher.
Keywords: Picture puzzles -- Juvenile literature